Revealing Practices of Fishermen Profit Sharing: An Ethnomethodology Study - Latuconsina, Fitriah Bidari; Triyuwono, Iwan; Mulawarman, Aji Dedi (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022)DO - 10.24843/JIAB.2022.v17.i01.p09, 2022)
This study aims to uncover the practice of profit sharing of fisherman in Yainuelo Village, Central Maluku Regency and the meaning behind the practice. This research uses a qualitative method with ethnomethodology approach. The instruments for the data collection are observation and interviews whereas the informants in this study are eight people who work on fishing boats. The obtained data then analyzed using indexicality and reflexivity analysis. The results showed that the Yainuelo fisherman practiced profit-sharing in seven stages namely, tahlilan (praying), cooperation agreement, fish catching, loading and unloading, selling, bage sala (profit sharing between the owner of the ship and the owner of the raft), and barekeng (profit sharing between the shipowner and the captain and crew). In practice, they not only share material (money) but also share prayers, share happiness, information to train skills that are interpreted as brotherhood, justice, honesty and a spirit of help. Keywords:  profit sharing, ethnomethodology, fishermen.